Teachers' Problems in The Perspective of Islamic Education Human Resource Management: Challenges and Solutions - Zahara, Sri; Oktavia, Lidya Fransiska; Yovica, Alia; Refnawati, Refnawati; Yuliani, Tri (COGNITIVISM: Journal of Educational Research and Development, 2025)
This article aims to analyze teacher problems in the perspective of Islamic education human resource management. This article uses the methodology of literature study to explore the various challenges faced by teachers in the context of human resource management of Islamic education. Databases such as Google Scholar are used to search for relevant sources of study, with search terms including "Islamic education," "teacher challenges," "human resource management," and "teacher retention in Islamic schools." Each selected study was analysed to assess the research design, context, and findings, to ensure a thorough review of existing research on teacher challenges. The results of the analysis show that the factors that cause the low professionalism of teachers in Indonesia include (1) there are still many teachers who do not pursue their profession, (2) the existence of teacher printing institutions that do not pay attention to how the output will be produced. and (3) lack of motivation of teachers in developing their quality. Solutions to overcome these problems include (1) organizing an effective teacher professionalism development program, (2) involving teachers in professionalism development programs, (3) improving competence through teacher certification programs, (4) improving teacher competence through training in the use of digital technology, and (5) encouraging teachers to be active in scientific activities